Pemanfaatan Platform Digital Berbasis Mobile Video Editing Bagi SDM Pariwisata di Desa Wisata Temajuk - Prihartini, Narti; Jagat, Lang; Mulyanto, U. Heri; Setiawan, Budi (PPPM POLTESA, 2024)
Sambas Regency has a lot of quite exotic tourism potential, starting from natural and cultural tourist attractions, this is due to the natural geographical conditions of Sambas Regency which support it and local cultural wisdom which is still maintained. Mountains, beaches, lakes and cultural attractions are the main attraction for tourists. One of the exotic tourism potentials that should be developed as a tourism business in Sambas Regency is Temajuk Village in Paloh District. Temajuk Village is a village that has a lot of tourism potential, especially natural tourism. In order to increase tourism potential in Temajuk Tourism Village, it is necessary to increase the capacity of Tourism Human Resources, especially in the use of digital platforms inpromoting and providing information related to tourist attractions in Temajuk Village. Promotion of a tourist attraction cannot be separated from digital promotion through several social media. Photography and videography are fields that need to be mastered in the digital era to create a creative, innovative and productive generation in accordance with the needs of industry in modern times like today. The aim of implementing the 2024 Iinternational Collaborative Community Services (ICCS) includes providing assistance to Tourism Human Resources in Temajuk Village in utilizing digital platforms that can be used to digitize Tourism Villages and promote tourism in Temajuk Village more efficiently by utilizing mobile video editing based on Capcut Mobile. This activity was attended by Temajuk Village Tourism Human Resources and had an impact on increasing digital tourism promotion capabilities using mobile based media as well as increasing the role of institutions in international collaboration to develop the country.